Anorogenic alkaline ring-type complexes of the Damaraland Province, Namibia, and their economic potential - Potgieter, J E (Rhodes University, Faculty of Science, Department of Geology, 1987)
Anorogenic alkaline ring-type complexes form within continental plate settings. Alkaline magmatism is derived from the upper mantle, in which mantle metasomatism plays an important part, as well as from partial melting of the lower crust. Radial and concentric fractures develop during the ascent of alkaline magma. Extrusion of basic and felsic magma takes place along these fractures with felsic volcanics building-up central volcanoes. As a result of emptying of the magma chamber, the superstructure of the volcano collapses and a caldera is formed. During the caldera stage syenitic and granitic material are intruded into ring fractures. Alkaline ring-type complexes may be classified as (i) alkaline qranite and syenite-type and (ii) carbonatite and undersaturated-type. These ring-type complexes occur as distinct igneous provinces. Some major provinces occur in Brazil, Corsica, Namibia, Nigeria, Norway, Saudi-Arabia and Sudan. In Namibia the Damaraland igneous province is of Mesozoic aqe and it contains 15 alkaline ring-type complexes . These complexes are situated along north-eastern trends which correspond to transform directions of the South Atlantic. During the opening of the South Atlantic (Gondwana breakup) Pan-African age lineaments were reactivated which allowed emplacement of anorogenic alkaline magmatism. A zonation of alkaline granite and syenitetype in the west and carbonatite and undersaturated-type ring-complexes in the east correlates with down- and upwarp axes parallel to the line of Gondwana fragmentation. Alkali- and Hâ º-metasomatism is related to the alkaline and syenite-type whereas alkali metasomatism (fenitization) is associated with carbonatite and undersaturated-type ring-complexes. Sn, W and Ta mineralization is associated with alkaline granites of some of the alkaline granite and syenite-type ring-complexes. Fe, F, POâ‚„ , Nb, Th, REE, Sr, Zn and Pb mineralization is associated with carbonatite complexes. Potential exists for: (i) porphyry Cu-Mo and epithermal-type (Au, Ag, Pt-metals, base metals) mineralization in the alkaline granite and syenite-type ring-complexes and (ii) disseminated Cu, Au, Aq and Pt-metals in carbonatite and undersaturated-type ring-complexes
Keywords: Alkalic igneous rocks -- Namibia